2002
DOI: 10.1007/s00464-001-8291-7
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of coagulation and fibrinolytic parameters in laparoscopic cholecystectomy

Abstract: These data suggest that laparoscopic surgery induces activation of coagulation and fibrinolytic pathways and, additionaly, betaTG elevation, which has never been reported and might account for postoperative platelet activation and a greater risk of thrombogenicity. Therefore, routine thromboembolic prophylaxis in patients undergoing laparoscopic surgery is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
5
25
1
1
Order By: Relevance
“…Similarly, after LC, Prisco et al demonstrated significant increases in prothrombin fragments (F1?F2) and Vecchio et al demonstrated significant increases in b-Thromboglobuline, PT, fibrinogen and D-Dimer values but these values were determined to be lower than the open surgery. These hypercoagulable results were attributed to high affinity of bThromboglobulin released from a granules due to thrombocyte activation and protein factor 4 to heparan sulfate in the endothelial membrane and denaturation in the membrane [13,14]. In our study, fibrinogen values were determined to be higher than the control group, while significant difference was not observed in D-Dimer parameter.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Similarly, after LC, Prisco et al demonstrated significant increases in prothrombin fragments (F1?F2) and Vecchio et al demonstrated significant increases in b-Thromboglobuline, PT, fibrinogen and D-Dimer values but these values were determined to be lower than the open surgery. These hypercoagulable results were attributed to high affinity of bThromboglobulin released from a granules due to thrombocyte activation and protein factor 4 to heparan sulfate in the endothelial membrane and denaturation in the membrane [13,14]. In our study, fibrinogen values were determined to be higher than the control group, while significant difference was not observed in D-Dimer parameter.…”
Section: Discussioncontrasting
confidence: 48%
“…Mild hypercoagulability was observed in patients who had undergone LC without thrombophilia. This informations may be evidence that at the subclinical level there is less intravascular clot formation with a laparoscopic than with a traditional surgical insult [12,14,21]. Protein S value was determined to be low in all groups except group D compared to the control group.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A better comprehension of the pathophysiology of this disease, has allowed the introduction of modern techniques for its treatment, including the recent minimally invasive techniques using tension-free tape. With the advent of laparoscopic surgery, which has been successfully performed with great advantages compared to the traditional techniques (5)(6)(7)(8), incontinence surgical repair has been also performed with this mini-invasive approach.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, laparoscopic surgery reduces alterations of general and immunological conditions of operated patients when compared to traditional surgery (5,6), probably reducing postoperative tumor growth (2,7).…”
mentioning
confidence: 99%